Keragaman dan Kelimpahan Arthropoda Tanah pada Tumpangsari Tanaman Cabai Merah, Jagung, dan Semangka - A. Nasruddin; Haerul HaerulU; Nurariaty Agus; Ahdin Gassa (Jurnal Agrotek Indonesia (Indonesian Journal of Agrotech), 2022)
Intercropping cropping patterns can increase the diversity and abundance of soil arthropods that can function as pest control for plants while maximizing land use. This study aims to determine the diversity and abundance of soil arthropods in the planting of monoculture chilies, intercropping with watermelon, chili intercropping with corn, and chili intercropping with corn and watermelon. The study was conducted in the Maros Regency, South Sulawesi Province, Indonesia. The study was conducted from August to November 2018. A sampling of natural enemy insects using pitfall traps installed for 1x24 hours with observational intervals every two weeks. From all of the cropping patterns, the soil arthropods that were found were spiders and several ant, namely: Odontomachus sp., Monomarium sp. and Anoplolepis sp. The insect diversity index was found to be low with an average of 0.07 in the chili cropping pattern intercropped with watermelon up to 0.17 in the monoculture chili cropping pattern and the chili cropping pattern intercropped with corn and watermelon. Soil arthropods that dominate in all types of cropping patterns were the Minimu monomorium ant species with the highest population of 2,987 individuals found in the chili cropping pattern intercropped with watermelons.